Investigations of the effect of SiC growth face on graphene thickness uniformity and electronic properties. (11th December 2014) - Pearce, Ruth; Tan, Xinran; Wang, Rui; Patel, Trupti; Gallop, John; Pollard, Andrew; Yakimova, Rositsa; Hao, Ling
Abstract: A study of the growth of graphene on the silicon-face (0001) and the carbon-face (000 − 1) of SiC is presented. The morphology and layer thickness is investigated using atomic force microscopy and scanning Kelvin probe microscopy and demonstrates the more wrinkled and less uniform thickness of the graphene growth on the C-face compared to the Si-face which shows uniform monolayer growth with some bilayer areas. Raman spectroscopy confirms the predominantly monolayer nature of the Si-face graphene and the inhomogeneous nature of the C-face graphene growth. Raman studies on the C-face show overlapping peaks as observed for spectra of Bernal-stacked graphene but we argue that the graphene is turbostratic with nanoscale differences in substrate effects leading to shifting of the Raman modes. Further samples show uniform scanning Kelvin probe maps of the carbon face along with very low bilayer coverage on the Si-face. Epitaxially grown graphene on the Si-face of SiC is reported to have a high carrier concentration and low mobility, however, van Der Pauw measurements demonstrate the low sheet resistance and relatively low carrier concentration of the graphene on the Si-face, in agreement with microwave measurements (Hao et al 2013 Appl. Phys. Lett. 103 123103 ) and scanning Kelvin probe maps which demonstrate the uniformity of the graphene.